Respuesta :

Answer:

Step-by-step explanation:

4). This is an exponential function.

5). Let the equation of this function is,

    f(x) = a(b)ˣ

    Since, two points (-1, 4) and (0, 6) are lying on the graph of the function,

    For (-1, 4),

    4 = a(b)⁻¹

    4 = [tex]\frac{a}{b}[/tex] --------(1)

    For (0, 6),

    6 = a(b)⁰

    a = 6

    From equation (1),

    4 = [tex]\frac{6}{b}[/tex]

    b = [tex]\frac{6}{4}[/tex] = 1.5

    Therefore, equation of the function will be,

    f(x) = 6(1.5)ˣ

6). Now the value of f(-4) will be,

    f(-4) = 6(1.5)⁻⁴

           = 1.185

ACCESS MORE